The lunar-tide cycle viewed by crustacean and mollusc gatherers in the State of Paraíba, Northeast Brazil and their influence in collection attitudes - Alves Rômulo RN; Nordi Nivaldo; Nishida Alberto K (BMC, 2006)
Abstract Traditional human communities have a wide knowledge of their environment. Collection of animals in estuarine and coastal areas are directly influenced by tidal cycles. The aim of this study is to evaluate the understanding of the tides associated with the lunar cycle held by people who gather crustaceans and molluscs in the State of Paraiba. The empirical knowledge of 20 crab gatherers and 30 mollusc gatherers was recorded through open interviews and structured questionnaires. The results showed that the gatherers have an accurate comprehension of tidal phenomenon based on their exploitation of natural resources, which perpetuates through generations.